8‐2: Invited Paper: Development of Active‐Matrix NanoLED Display Using Heavy‐Metal‐Free QDs Patterned by Photolithography Process. Issue 1 (28th June 2022) - Nakanishi, Yohei; Kanehiro, Masayuki; Okamoto, Shota; Matsushita, Kazuhiko; Horiue, Shinichi; Utsumi, Hisayuki; Qu, Yang; Fu, Xiaihuan; Konishi, Katsuhiko; Oda, Akihiro; Kitagawa, Makoto; Ishida, Takeshi; et al.
Abstract : We report and discuss the challenges to realize a nanoLED based display from the perspective of materials and processes. Additionally, we report on an active‐matrix nanoLED display using heavy metal free Quantum Dots (QDs) patterned by photolithography, realized by combining materials and process technology.